Bluestocking Feminism and British-German Cultural Transfer, 1750-1837 - Johns, Alessa (University of Michigan Press, 2014)
Bluestocking Feminism and British-German Cultural Transfer, 1750-1837 examines the processes of cultural transfer between Britain and Germany during the Personal Union, the period from 1714 to 1837 when the kings of England were simultaneously Electors of Hanover. While scholars have generally focused on the political and diplomatic implications of the Personal Union, Alessa Johns offers a new perspective by tracing sociocultural repercussions and investigating how, in the period of the American and French Revolutions, Britain and Germany generated distinct discourses of liberty even though they were nonrevolutionary countries. British and German reformists-feminists in particular-used the period's expanded pathways of cultural transfer to generate new discourses as well as to articulate new views of what personal freedom, national character, and international interaction might be.